2018
DOI: 10.11604/pamj.2018.30.167.14261
|View full text |Cite
|
Sign up to set email alerts
|

Non-clinical isolates as potential reservoirs of antibiotic resistance in Port Harcourt, Nigeria

Abstract: IntroductionMultidrug resistance (MDR) is a growing problem worldwide. This type resistance often arises due to the sequential acquisition of drug resistance determinants and subsequent clonal spread. It is therefore important to determine possible reservoirs of these MDR gene to help set out control strategies. This study was aimed at analysing susceptibility patterns of various non-clinical Gram negative bacterial strains to determine their potential as reservoirs of MDR.MethodsThirty-five non-clinical Gram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The results of this study were in parallel with the previous studies from Australia, China, and Switzerland that were suggestive of the ability of resistant GNB to cause a public health problem through the food chain, especially in climes where antibiotics are used irrationally in non-clinical practices [ 17 20 ]. In this study, the high resistance rates (> 70%) against third-generation cephalosporins (TGCs) were similar to previous report by Otokunefor et al [ 21 ] from Nigeria who reported a resistance rate of ≥80% against TGCs family. Also, in accordance with the findings of this study, a high resistance rate against quinolones/fluoroquinolones was reported previously by a research from Romania [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study were in parallel with the previous studies from Australia, China, and Switzerland that were suggestive of the ability of resistant GNB to cause a public health problem through the food chain, especially in climes where antibiotics are used irrationally in non-clinical practices [ 17 20 ]. In this study, the high resistance rates (> 70%) against third-generation cephalosporins (TGCs) were similar to previous report by Otokunefor et al [ 21 ] from Nigeria who reported a resistance rate of ≥80% against TGCs family. Also, in accordance with the findings of this study, a high resistance rate against quinolones/fluoroquinolones was reported previously by a research from Romania [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Enterobacteriaceae are typically found in animals and the environment (Otokunefor et al, 2018) and have been reported as reservoirs of resistance genes that could be passed to other bacterial cells in the system. The use of antibiotics in livestock production results in an increase in antibiotic resistant strains in people (Bevan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This study provides detailed genomic characterization of antibiotic resistance in bovine animal and environmental Enterobacteriaceae isolates for Nigeria. A number of previous Nigerian studies described the detection, frequency/prevalence of resistance to antibiotics in livestock and the environment using phenotypical techniques (Ayandiran et al, 2014;Onuoha, 2017;Otokunefor et al, 2018;Ugwu et al, 2018). Only a few Nigerian studies have been able to explore the genetic mechanisms of antibiotic resistance in bovine animals and the environment (Olowe et al, 2015;Sharma et al, 2017;Adelowo et al, 2018;Ayandiran et al, 2018;Ejikeugwu et al, 2018) which is important to understand the dissemination of resistant isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that plasmid maintenance is improved by presence of a selective pressure, this could indicate a higher use of antimicrobials in non-clinical rather than clinical settings. Non-clinical bacteria of medical importance have previously been noted to serve as possible reservoirs of MDR and the negative implications of the possible transfer of resistance genes between different bacterial types and from animal to human strains elucidated (Otokunefor et al, 2018, Seiffert et al, 2013, Card et al, 2017. Furthermore, such spread via plasmids has been demonstrated but in vivo and in vitro (Keelara and Thakur 2014, Martin et al, 2014, de Been et al, 2014, Card et al, 2017.…”
Section: Discussionmentioning
confidence: 99%